2013
DOI: 10.2138/rmg.2013.75.8
|View full text |Cite
|
Sign up to set email alerts
|

Carbon in the Core: Its Influence on the Properties of Core and Mantle

Abstract: Earth's earliest history was marked by accretion from protoplanetary materials and segregation of the core within about 35 m.y. (Kleine et al. 2002;Yin et al. 2002) and formation of the Moon by giant impact approximately 100 m.y. after the origin of the solar system. During this primary differentiation, all elements were distributed between the Fe-rich metallic phase and the silicate mantle according to their partition coefficients D i (D i = [i] metal /[i] silicate ). The net result is that the mantle is rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 92 publications
7
106
0
1
Order By: Relevance
“…It is not precisely known how much of which elements the core contains besides Fe and Ni, but the most likely suspects are C, S, O, and Si, because they are common and abundant elements in the Sun and in planets and are known to form alloys with Fe at high pressure and temperature. 83 A conservative estimate is that the Fe-Ni alloy in the core contains about 0.2% by weight carbon. Because the mass of the core is 2 × 10 12 Gt, it therefore contains about 4 billion GtC, which constitutes about 90% of the Earth's carbon (and 1 million Figure 5.…”
Section: The Natural Carbon Cycle(s)mentioning
confidence: 99%
“…It is not precisely known how much of which elements the core contains besides Fe and Ni, but the most likely suspects are C, S, O, and Si, because they are common and abundant elements in the Sun and in planets and are known to form alloys with Fe at high pressure and temperature. 83 A conservative estimate is that the Fe-Ni alloy in the core contains about 0.2% by weight carbon. Because the mass of the core is 2 × 10 12 Gt, it therefore contains about 4 billion GtC, which constitutes about 90% of the Earth's carbon (and 1 million Figure 5.…”
Section: The Natural Carbon Cycle(s)mentioning
confidence: 99%
“…The first one is the single stage model or equilibrium model, in which chemical equilibrium between the core and the mantle is thought to be achieved at certain P-T conditions at the base of the magma ocean (Li and Agee, 1996;Righter, 2011 The second endmember mode is the continuous core formation model (Wood et al, 2006(Wood et al, , 2013. In this model, Earth accretion and the delivery of coreforming metal occur in small steps of 1 % mass with constant metal/silicate ratio.…”
Section: Resultsmentioning
confidence: 99%
“…In each step the metal equilibrates with the silicate magma ocean, and it remains chemically isolated once it segregates in the core. The fractionation of light element isotopes in this model can best be described by the Rayleigh distillation model (Wood et al, 2013;Horita and Polyakov, 2015) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…During the differentiation into core and mantle, this carbon could partly be dissolved in the core material, leaving a mantle depleted in carbon. This is derived from recent studies that found that the outer core of Earth may contain some carbon at the 1% weight level (Nakajima et al 2015;Wood et al 2013). 6.…”
Section: Carbon Content Of Planetesimalsmentioning
confidence: 99%